2010
DOI: 10.1155/2011/459531
|View full text |Cite
|
Sign up to set email alerts
|

A Chinese Herbal Decoction, Modified Yi Guan Jian, Induces Apoptosis in Hepatic Stellate Cells through an ROS‐Mediated Mitochondrial/Caspase Pathway

Abstract: The Chinese herb modified Yi Guan Jian (mYGJ) is an effective regimen that is usually used in outpatients with chronic liver diseases such as fibrosis and cirrhosis. However, the mechanism for the action of mYGJ on liver fibrosis is not yet clear. In this study, we found that mYGJ induced hepatic stellate cells (HSCs) apoptosis concomitant with the downregulation of Bcl-2 expression and slight elevation of Bax level. Moreover, the reactive oxygen species (ROS) were generated in the early stages of mYGJ-induced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 29 publications
1
16
0
Order By: Relevance
“…6) in proportion to the reduced production of collagens and stellate cell activity. This result is consistent with results obtained by Lin et al, 2011a, b that showed Yi Guan Jian (YGJ) reduced collagen deposition in the DMN model of hepatic fibrosis. The reduced fibrosis was associated with reduced alpha-SMA expression and type I procollagen expression in the liver.…”
Section: Discussionsupporting
confidence: 92%
“…6) in proportion to the reduced production of collagens and stellate cell activity. This result is consistent with results obtained by Lin et al, 2011a, b that showed Yi Guan Jian (YGJ) reduced collagen deposition in the DMN model of hepatic fibrosis. The reduced fibrosis was associated with reduced alpha-SMA expression and type I procollagen expression in the liver.…”
Section: Discussionsupporting
confidence: 92%
“…As shown in Figure c,d, a dose‐dependent increase in early apoptotic (annexin V+/PI−) cells in the presence of paeonol was observed and that paeonol at 20 μmol/L resulted in significant apoptosis. The mitochondria play a crucial role in cell apoptosis pathway . Treatment with paeonol caused HSCs to loss the mitochondrial membrane potential in a dose‐dependent manner (Fig.…”
Section: Resultsmentioning
confidence: 95%
“…The extract was decanted, filtered under vacuum, concentrated in a rotary evaporator, and then lyophilized. The concentration for final stock solution of YGJ extract was 175 mg/ml (Lin et al, 2011).…”
Section: Herbal Medicinementioning
confidence: 99%
“…Furthermore, HSC apoptosis may also play a central role in the spontaneous recovery from biliary fibrosis (Issa et al, 2001). Therefore, it is important to discover the apoptosis mechanisms of HSC treated by traditional Chinese herbal medicines that might resolve progressive HSC proliferation and matrix synthesis (Lin et al, 2011).…”
Section: Introductionmentioning
confidence: 99%